COVER NITROGEN FERTILIZATION ON THE COMMON BEAN IN NO-TILLAGE SYSTEM - PIASKOWSKI, Sérgio Roberto (Scientia Agraria, 2000)
Field trials were carried out in the agricultural years of 1996/97 and 1997/98 at the State University of Ponta Grossa Scholl and at the Agricultural High School Farm of Palmeira, respectively, both of them under no tillage system for eight years, with the aim of study nitrogen fertilization for bean culture under no tillage system. YieId, their components, plant morphological rnodifications and dry matter were evaluated. The experimental design employed was a randomized complete block, six treatments (0, 20, 40, 60, 80 and 100 kg.ha-1) and five replications with me FT Nobre as indicator variety. The experimental plots were six limes with 6,00 m each and 0,45 m among them, in the trial carried out at Ponta Grossa, and 0,40 m among the lines in the trial carried out at Palmeira. Two lines were left out, leaving with a usable area of 4,50 m2 and 4,80 m2 for the experiments carried out at Ponta Grossa and Palmeira, respectively. to evaluate the yield. Ten plants were harvested to evaluate dry matter during the V2 to R8 stages. In addition to dry matter, morphological characteristics, yield and their components were evaluated at the R4 stage. At Palmeira evaluated dry matter and morphological characteristics were evaluated from V2 to R8 stages, to R9 stage in addition these evaluations yield and their components were evaluated too. The best result was obtained at the higher nitrogen dosis 100 kgha-1 and its production was 2.207 kg.ha-1 and the worst result was 1.614 kg.ha-1 at Ponta Grossas trial.